Creating a Framework for Public-Private Partnership Programs : A Practical Guide for Decision-makers - Delmon, Jeffrey (World Bank, Washington, DC, 2015)
Public private partnerships (PPP) represent an approach to procuring infrastructure services that is radically different from traditional public procurement. It moves beyond the client-supplier relationship when government hires private companies to supply assets or a service. PPP is a partnership between public and private to achieve a solution, to deliver an infrastructure service over the long term. It combines the strength of the public sector’s mandate to deliver services and its role as regulator and coordinator of public functions with the private sector’s focus on profitability and therefore commercial efficiency. There is a tendency to approach reform of the PPP framework as a single action, generally delivered by external consultants in one massive report, with a few workshops and training sessions (in an effort to deliver the guidance in a more digestible form). Achieving a viable PPP framework involves a complex series of parallel, iterative initiatives, and efforts. It involves updating the different elements of the PPP framework discussed in this text as each new lesson is learned from PPP transactions as they are implemented and national best practice as it develops. Section one introduces the framework required to support PPP and provides a summary of the text. Sections two to six describes five key elements of the PPP framework and what the government can do to improve them.